Patient-derived rectal cancer organoids—applications in basic and translational cancer research - Yan, Yumeng; Cheong, Io Hong; Chen, Peizhan; Li, Xiaoguang; Wang, Xianli; Wang, Hui (Frontiers in Oncology, 2022)
Colorectal cancers (CRCs) are among the most common cancers diagnosed and the leading cause of death both in men and women. Rectal cancer (RC) is particularly challenging compared with colon cancer, as a large number of deaths from rectal cancer are misclassified as colon and the treatment after diagnosis is more complex because of tumor location in the pelvis and close to genitourinary organs. Early diagnosis and multiple treatment strategies have optimized outcomes for individual patients. However, the heterogeneity in clinical response and the morbidity associated with radical surgery highlight the need for more accurate and precise model to facilitate RC research like predict response to standard therapies. Organoids generated from adult stem cells or tissues have developed as powerful models to recapitulate many aspects of their primary tissue, consisting of 3D self-organizing structures, which shed great light on the applications in both biomedical and clinical research. As the preclinical development of treatments for RC has historically relied on colon cancer cell lines, research on patient-derived RC organoid models allow the in-depth analysis of tissue function, development, tumor initiation, and cancer pathobiology. In this review, we discuss the different applications of patient-derived RC organoid in basic cancer biology and clinical translation in the past two years, including sequencing analyses, drug screening, targeted therapy testing, tumor microenvironment studies, and genetic engineering capabilities.